Influencing Factors of Intention of Undergoing Pap Testing among Unmarried Nurses - Hae Won Kim (Korean Society of Women Health Nursing, 2014)
PURPOSE: This study was to assess the intention of undergoing Pap testing and to identify influencing factors of HPV knowledge and their attitude related to Pap test by sexual activity among unmarried nurses. METHODS: A cross sectional survey design was employed, utilizing a self-administered questionnaire amongst 343 unmarried nurses. Descriptive statistics was utilized to analyze data and inferential statistics used an independent-t test and chi2 test for the differences in measurement variables, and odds ratios for factors on intention of Pap testing by sexual activity. RESULTS: Nurses not sexually active were significantly higher in intention of Pap testing (chi2=40.15, p<.001) and influencing factors of HPV knowledge (t=3.93, p=.048) than did nurses who were sexually active. Factors influencing intention were regularity of the breast self-examination (Adjusted Odds Ratio [AOR]=4.20, 95% Confidence Interval [CI]=1.93~9.17), HPV knowledge (AOR=2.49, 95% CI=1.36~4.56), and attitudes toward the Pap test(AOR=2.33, 95% CI=1.25~4.34) amongst nurses who never had sexual experience. CONCLUSION: It is necessary to minimize negative attitudes of Pap testing and to increase HPV knowledge in order to improve intention of Pap testing for women who were not sexually active. More focus would be given to sexually active women to get Pap tested as a preventive measure for cervical cancer.